E Efektivitas Terapi Slow Deep Breathing Dan Terapi Murottal Al-Qur’an Terhadap Penurunan Tingkat Kecemasan Pada Lansia - Fadillah, M.; Suwandewi, Alit; Dewi Anjani, Amellia (Journal of Nursing Invention, 2024)
Background: The elderly people often feel anxious, anxiety itself can be caused by negative thoughts or bad events that have happened in the past. If it always happens and often, it will interfere with activities, it is called anxiety disorder. Some relaxation methods carried out in this study to reduce anxiety are the Slow Deep Breathing technique and with accompanying therapy, namely listening to surah Al-Kahf verses 1-10. Objective: This study aims to reduce anxiety in the elderly with the intervention of Slow Deep Breathing therapy and Murottal Surah Al-Kahf therapy (verses 1-10). Method: This scientific work uses a single case study design on elderly clients with anxiety problems, with the assessment of anxiety hamilton anxiety rating scale (HARS). Result: The results obtained after the provision of Slow Deep Breathing therapy and Murottal Surah Al-Kahf therapy (verses 1-10) as superior interventions for elderly clients experiencing anxiety. Researchers carried out the intervention for three days and with a duration of ± 20 minutes, the intervention was carried out once / day. The results of the first day pre-test score 40 (severe anxiety). The last day with a post-test score of 13 (mild anxiety). Conclusion: The conclusion obtained was a significant decrease in anxiety after being given Slow Deep Breathing therapy and Murottal Surah Al-Kahf (verses 1-10) included with the meaning of the verses for three consecutive days, the client said he felt relieved and was able to manage thoughts and feelings within himself.